A Comparative Study on Multicultural Attitude of University Students: Austria, Hungary and Turkey Sample - Karatekin, Kadir; Akcaoğlu, Mustafa Öztürk; Taban, Muhammet Hayati (Journal of History Culture and Art Research, 2019)
Increasing diversity within European countries has led the policy makers and the public to question the place of immigrants in society. Classrooms are becoming multicultural growingly as the migrants increase and mobility among countries becomes easier. Moreover, the number of diversities and cultural differences brought by the refugee students have raised. To this end, in this study, we aim to reveal and compare the multicultural attitudes of university students studying in different countries. A total of 356 university students from Turkey, Austria and Hungary participated in the study. In order to collect data, The Munroe Multicultural Attitude Scale Questionnaire (MASQUE) was used. The results revealed that there is a significant difference among the countries in terms of multicultural attitude, gender and political views of the participants. According to the findings, while Austria has the highest score in terms of multicultural attitude, Hungary has the lowest score. In addition, Austrian university students have the highest total score of multicultural attitude and know sub-dimension while Turkish university students have the highest scores of care and act sub-dimensions. Furthermore, it can be said that living/studying in an EU member country does not necessarily mean that university students have a high level of multicultural attitude.